200 years of the University of Warsaw. Events, symbols and students = - Tyszkiewicz, Adam (CIAN-Revista de Historia de las Universidades, 2016)
The following article displays a brief history of the University of Warsaw. Its history commenced officially in 1816, when Tsar Alexander I stipulated the University foundation decree. Although initially the structure was rather minor and consisted of only five faculties, it performed a great role in development of Polish culture, art and science. Within its walls the virtuoso pianist, Frederic Chopin received an excellent education and many distinguished professors, including Ludwik Osinski and Fryderyk Skarbek delivered lectures. The University was located in one of the most beautiful parts of the city, in place of a former 17th century royal residence. Following examples of other European schools, the University of Warsaw has been very soon given an emblem, a banner, the insignia, and its authorities and professors were to wear academic robes. The University was closed down for the first time after the fall of the 1831 Uprising. It was later on, in 1862, reactivated for seven years under the name of the Main School. After just a short period of existence, the Polish institution was replaced by a Russian-language Imperial University and The University of Warsaw was not revived until 1915. As evidenced by the text, the subsequent years were a difficult period for the University, as it was dominated by conflicts between the Polish people and German invaders during the First World War and afterwards by the outbreak of the Polish-Bolshevik War in 1918, in which many students were involved. The institution started properly operating again in 1921. In the interwar period a number of distinguished scholars worked for the University, i.e. Kazimierz Michalowski, an archaeologist and Waclaw Sierpinski, a mathematician. The development of the University was impeded once again by the outbreak of the Second World War. Unfortunately, during that time many famous Polish professors were killed and some university buildings turned to rubble. Currently, the University of Warsaw is the largest academic institution in Poland with nearly 45 thousand students in the academic year of 2015/2016. This year, the institution celebrates its bicentenary under the slogan “Two centuries, a good beggining.” This is also the idea the University of Warsaw intends to follow in the near future.